New candidates for treatment and management of carpal tunnel syndrome based on the Persian Canon of Medicine - Mohammad Setayesh; Arman Zargaran; Amir Reza Sadeghifar; Mehdi Salehi; Hossein Rezaeizadeh (Integrative Medicine Research)
Carpal tunnel syndrome (CTS) is defined as a compressing median mononeuropathy. CTS is one of the major costly debilitating diseases of the hand. Although CTS is a relatively recent concept in current medicine, some evidences show that medieval physicians in Persian medicine (PM) such as Avicenna were familiar with it. The PM textbook written by Avicenna, the Canon of Medicine, defines the anatomy of carpal tunnel and median nerve, as well as mononeuropathy; it also offers suggestions for the prevention and treatment of carpal tunnel syndrome (called as Vaja al-asab and Khadar) in the chapter of nerve diseases. The book describes not only symptoms including pain, paresthesia, hypoesthesia, tingling, and numbness, but also its etiology such as nerve compression (entrapment neuropathy); nonphysical reasons such as disturbed balance among the four body humors; alteration in the nerve's temperament (Mizaj) that prevents the transmission of nerve impulses; and the others such as nutrition, mental condition, sleep, weather condition, body movements, and proper disposal of body waste. Furthermore, the book suggests a lifestyle modification method based on six factors and 10 prescriptions composed with 85 natural products that are not actively used for CTS treatment in modern times. The medicinal suggestions for CTS in the Canon of Medicine will be good candidates for discovering new treatments besides providing historical significance to the various insights considered 1000 years ago. Keywords: Carpal tunnel syndrome, History of medicine, Neurology, Persian medicine